Pembinaan Karakter Siswa Melalui Program Islamic Studies di SD Bosowa Al-Azhar Cilegon - Nanda Lidiana; Firman Robiansyah; Darmawan Darmawan (Pedagogi: Jurnal Ilmu Pendidikan, 2022)
Education plays a role in character building. This study aims to determine, analyze, and describe the implementation of the Islamic Studies program, character values, and the implications of the Islamic Studies program on student character building. This research is a qualitative research with case study method. Data collection used: observation, interviews, documentation studies, and questionnaires. Based on the results of the study, it was concluded that: 1) in limited face-to-face learning, the implementation of the Islamic Studies program went well, 2) the character values ​​in the Islamic Studies program included: religious, hard work, responsibility, fond of reading, disciplined, independent, love peaceful, appreciative of achievement, and communicative, 3) the implementation of the Islamic Studies program has significant implications for the character building of students with 84% of students responding correctly and 16% of students answering incorrectly. The Islamic Studies program is recommended for other schools as an effort to build character.